PERCEIVED SOCIAL SUPPORT DAN SELF-COMPASSION DENGAN DISTRES PSIKOLOGIS REMAJA AKHIR - Noor Safira, Tasya; Indrawati, Erdina (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
The objective of this study is to ascertain the relationship between Perceived Social Support and Self-Compassionwithpsychological distress in late adolescents. The research subjects were 165 students of class XI at SMA Pusaka 1in East Jakarta, selected using the simple random sampling technique with a quantitative method. The data werecollected using an online questionnaire comprising three Likert scales. The scales used to measure the variables ofinterest were the Psychological Distress Scale, the Perceived Social Support Scale, and the Self-Compassion Scale.Psychological distress was assessed using the Hopkins Symptom Checklist (HSCL-25), while Perceived SocialSupport was evaluated using the Multidimensional Scale of Perceived Social Support (MSPSS), and Self-Compassion was gauged using the Self-Compassion Scale (SCS). The results of the bivariate and multivariateanalyses conducted using the JASP (Jeffrey's Amazing Statistics Program) 19.0 version for Windows revealed asignificant negative relationship between Perceived Social Support and psychological distress, with a correlationcoefficient (r) of -0.530 and a p-value of less than 0.001. Furthermore, a significant negative relationship wasidentified between self- compassion and psychological distress, with a correlation coefficient (rho) of -0.204 and ap-value of 0.009. The results of the stepwise regression analysis indicated that Self-Compassion was a moredominant predictor of reduced psychological distress than Perceived Social Support. Consequently, this studyemphasises the importance of developing Self-Compassion and Perceived Social Support in order to reduce the levelof psychological distress in lateadolescents in a school setting.